Evaluation of Lung Cancer Risk from Incense Burning and Nitrogen Dioxide Exposure through Meta-analyses and Molecular Docking - Hui Wen, Tang (Universiti Malaysia Sarawak, 2025)
Lung cancer (LC) remains a leading cause of cancer mortality worldwide, with environmental exposures playing a pivotal role in its aetiology. Nitrogen dioxide (NO2), a primary toxicant released both from incense combustion and outdoor air pollution (AP), has been increasingly implicated in LC risk. To address this, three interlinked approaches were undertaken. First, a meta-analysis of case-control studies in Asian populations demonstrated that incense burning, a significant indoor source of NO2 and other carcinogens, is associated with increased LC risk (pooled odds ratio [OR] = 1.33, 95% confidence interval [CI]: 1.20-1.48). Second, a meta-analysis of cohort studies beyond European countries suggested that NO2 exposure is associated with elevated LC incidence and mortality (pooled hazard ratio [HR] per 10 parts per billion (ppb) increase in NO2 = 1.08, 95% CI: 1.03-1.13). Third, molecular docking analyses were conducted to elucidate the mechanistic basis of these associations, revealing that NO2 and its reactive surrogates, including peroxynitrite (ONOO⁻), 2-nitrophenol (2-NT), 3-nitrotyrosine (3-NT), and nitrobenzene, exhibit binding affinities with proteins central to oxidative stress, inflammation, and oncogenic signalling pathways implicated in LC pathogenesis. In conclusion, these findings provide converging evidence that NO2, whether derived from indoor sources such as incense burning or from outdoor AP, contributes to lung carcinogenesis through both epidemiological associations and molecular interactions.